Motivation of Croatian Foreign Language Students in the Out-of-school Context: a Comparison of English and German - Karlak, Manuela (Slavia Centralis, 2024)
This article examines the concept of motivation and its role in foreign language learning. In addition to the theoretical basis and an overview of the relevant research, a small-scale quantitative research among English and German language and literature students is used to identify potential differences in motivated behavior in the out-of-school context and in self-assessment of language competence. The results of the statistical analysis show that these two variables correlate positively with each other and that, compared to German studies students, English studies students exhibit significantly more foreign language motivated behavior in the form of various activities in the out-of-school context and rate their language competence significantly higher. The results point to the multi-layered and complex nature of motivation and are interpreted in the context of the Croatian formal education and the broader social context.
Keywords: motivated behavior, foreign language, students, activities